Analisis Kepuasan Pelayanan Rumah Sakit Umum Sari Asih - Tri Amanah; Putri Arifani; Syamsul Hidayat (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
A hospital is a professional health institution whose services are provided by doctors, nurses and other experts. Sari Asih Hospital has many branches, one of which is in Serang City. The facilities available at this hospital are very diverse, starting from: parking lot, canteen, mosque, toilet, treatment room, and many more listed at this hospital.The layout of the room is neatly arranged and in accordance with the floor plan listed in this hospital. Many workers are ready to serve the people who visit this hospital. Not only people who live in the city of Serang, but in every city, district and even areas that are far away also visit for treatment at this hospital.This hospital already has a good name, so people continue to visit this hospital. Sarih Ssih Hospital accepts the Social Security Organizing Agency (BPJS) and the medicines it provides do not differentiate between people who use public or private insurance. The analysis of this research is to evaluate the services available at Sari Asih Hospital so that in the future it will be even better, so that people feel satisfied after visiting Sari Asih Hospital.